The Impact of Political Violence on the Political Process in Iraq 2018-2023 - Majeed, Dr. Delaware Othman Majeed (Sulaimani Journal for Humanities, 2025)
The phenomenon of political violence in Iraq is a complex structural crisis, meaning that there is a problem in the composition and structure of society, in all social, political, cultural, economic and value aspects, which together contributed to generating violence in the form we see today. We can say that political violence in Iraq as a phenomenon was not born from a vacuum or nothingness, but rather there were inputs and factors that produced it. Among them: the problem of control and seizure of power, and the negative effects and repercussions of the disadvantages of sectarian democracy that was established in Iraq after 2003. In the last five years (2018-2023), some manifestations of political violence caused an obstruction of the progress of the political process in Iraq in a constitutional and legal manner, as it led To the deterioration of security and stability in some governorates, in addition to the decline in confidence in the formation and work of the government and existing constitutional institutions. Political violence also disrupted dialogue and constructive understanding between the various political parties.
Keywords: Political Violence; Political Process; Violence Manifestations; Political Influence; Conflict Dynamics